Fee Payment System in SMK PUSPITA BANGSA using Microsoft Visual Basic 6.0 - Sari Agustin; Marzuki Marzuki., SKom., MMSI (Jurnal Sistem Informasi, 2007)
The development of increasingly sophisticated computer very helpful in data processing still using manual systems. This is often a problem associated with data accuracy resulting in delays in processing the data. The information is valuable information quickly and accurately. So in need of a computerized system as supporters. Fee Payment System in Vocational High NATION PUSPITA designed with the aim to obtain and process information quickly and accurately as well as secure data storage. So that the final results are useful in decision making.